The Contribution of Tiktok Bilingual Post in Enhancing Students Vocabulary - Yuniati, Anita Tyas; Sujatmiko, Sujatmiko (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
This research has two objectives: 1)To know the translation techniques used in bilingual TikTok posts. 2)To describe the TikTok learning media to increase students' vocabulary. Research method used is a classroom action research. Data collection carried out in five ways: observation, interviews, field note, tests and documentation. This research also took data from TikTok to analyze the translation technique. Data analysis was done by data reduction, data presentation and conclusion drawing or verification. Data validity was done by method triangulation technique. Subjects of this research were students of class VII C at SMP Muhammadiyah 3 Yogyakarta. Object of this research is vocabulary mastery. Results of this research show positive results that the use of TikTok bilingual posts can help improve the vocabulary mastery by students. The increase is seen from the calculation of the percentage of student passed KKM, pre-test 41.93%, post-test 1 51.61% and post-test 2 93.54%. Test results are supported by the results of interviews with students. Interview results stated according to the students, learning using TikTok media helped in improving vocabulary. In addition, results of the analysis of translation techniques in 69 sentences from TikTok posts show that there are four types of translation techniques used, establish equivalent, borrowing, amplification and description. Based on the results of this research, it can be concluded that the use of TikTok bilingual posts as learning media at SMP Muhammadiyah 3 Yogyakarta can help improving students' vocabulary and has a positive response